Exploring the opportunities and perceived success of internationalization strategies in Malaysian SME’s - Hussain, Fawad; Mubarak, Saleh; Hassan, Mohamad Ghozali; Mohtar, Shamimi (College of Law, Government and International Studies, Universiti Utara Malaysia., 2010)
There is a complete transforming process all around the global economy. Technological displacement is displacing all the business activities into information oriented or information based activities. Internationalization has the great contribution in the fundamental changes which took place all over the world. In fact due to internationalization a revolution has been introduce globally. Due to the web there is availability of extended opportunities for Malaysian customer and small & medium enterprises (SME‟s). There is a need of an orderly frame work, due to limited research on the role of internet in international marketing. In order to have the better understanding to the role of internet in international marketing strategy, it is needed to examine the purpose for which SME‟s use the internet in the international marketing context(Shanker & Meyer, 2009). This paper will be providing a significant contribution in the development of internationalization process among Malaysian SME's. This paper will also help Malaysian SME's to improve their internationalization strategies in contrast with the electronic commerce.